PHYTOCHEMICAL CHARACTERIZATION AND ANTICANCER POTENTIAL OF QUISQUALIS INDICA L.: AN IN SILICO APPROACH - AJAY KUMAR VERMA; AKS RAWAT (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The aim is to isolate and identify the bioactive molecules of Quisqualis indica, to analyze their chemical profiles and to evaluate their anti-tumor activity by targeting the proteins in question. Methods: The leaves of Q. indica were collected, identified, and extracted with 50% hydroalcohol by means of the Soxhlet method. The extract from the crude oil was fractionated and quisqualic acid isolated by means of silica gel and Sephadex LH-20 chromatography. Chemical profiling was carried out by means of high-performance liquid chromatography-diode array detector-electrospray ionization mass spectrometry (HPLC-DAD-ESI/MS), Fourier transform infrared (FTIR), and proton nuclear magnetic resonance (NMR). Molecular docking of quisqualic acid to tumor-associated proteins (2PIO, epidermal growth factor receptor, human epidermal growth factor receptor 2, vascular endothelial growth factor receptor 2, mammalian target of rapamycin, programmed death-ligand 1) has been performed with the help of the SwissDock and Discovery Studio Visualizer. Results: The presence of quisqualic acid was confirmed by HPLC-DAD-ESI/MS analysis, as evidenced by its retention time at 5 min, a ultraviolet absorbance maximum at 230 nm, and a characteristic MS fragmentation pattern, including a deprotonated molecular ion (M–vH)⁻ at m/z 146 and MS2 fragment ions at m/z 84, 102, and 112. Functional analyses, such as FTIR, and NMR confirm the presence of major functional groups such as hydroxyl groups and aromatic substances. In silico docking revealed a moderate-to-high binding affinity for quisqualic acid to cancer-related receptors such as androgen receptor (−6.010 kcal/mole) and VEGFR2 (−5.456 kcal/mole), which implicates quisqualic acid in the treatment of prostate cancer and angiogenesis. Conclusion: Q. indica has an immense anticancer potential, particularly against the target tumors of the prostate and colorectal cancer. Its active ingredient, quisqualic acid, has good binding properties and merits further investigation in vivo and in clinical trials.